SUSTAINABLE TECHNOLOGIES:WASTE TO ENERGY SOLUTIONS - Joshi, Poonam; Sharma, Siddhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
By tackling the twin issues of rising waste generation and the demand for sustainable energy sources, waste-to-energy (WtE) technologies provide a revolutionary solution to trash management and energy generation. These creative technologies turn a variety of waste materials—such as industrial byproducts, agricultural residues, and municipal solid trash—into useful energy sources including heat, electricity, and biofuels. Anaerobic digestion, gasification, and incineration are the three main procedures used in WtE. Through high-temperature combustion, waste is greatly reduced in volume and heat is produced for power production. Compared to conventional incineration, gasification provides a cleaner and lower-emission option by partially oxidizing organic materials to create synthetic gas, or syngas. Without oxygen, anaerobic digestion breaks down organic materials to produce power or warmth. Each technique reduces reliance on landfills while simultaneously reducing greenhouse gas emissions by replacing the use of fossil fuels. Beyond just reducing trash, WTE technologies also improve energy security by supplying renewable energy sources and promoting a circular economy through resource recovery. Nonetheless, obstacles like the intricacy of technology and the requirement for efficient garbage sorting continue to be crucial factors for broad adoption. All things considered, WTE technologies are becoming increasingly important in the fight for sustainable development and greener cities as urban areas continue to struggle with waste management difficulties.